"You can go out 14 miles away with the knowledge that you've got the battery to help you back if you need it!" Narratives of ranging behaviour and wellbeing in diaries of e-bike trial participants. Issue 2 (2022) - Jones, Tim; Spencer, Ben; Beale, Nick; Leyland, Louise-Ann; Reekum, Carien M. van
No abstract available